PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF CANVA TERHADAP KEMAMPUAN LITERASI MATEMATIKA BERBASIS BUDAYA MELAYU DENGAN MODEL PEMBELAJARAN STAD - Khairin Nawangsih; Risna Mira Bella Saragih; Minta Ito Simamora (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
This study aims to produce a valid, practical and effective Canva Interactive Learning Media product based on Malay culture on the material of linear equation systems and inequalities of one variable. Also to determine the level of mathematical literacy skills at SMP Negeri 3 Tanjung Beringin. This type of research is a Research and Development (R&D) development study. The subjects used in this study were 32 students of class VIII SMP Negeri 3 Tanjung Beringin. The analysis of the Canva interactive learning media value from media validator experts was 78.5% with very good or valid criteria for use. For material experts with a percentage of 78%, the category is Very valid. The classification of the teacher's practicality questionnaire meets very practical with a percentage of 94% and the student response questionnaire score gets an average of 90% categorized as very practical to use. Effectiveness is obtained from the results of the N-Gain calculation, a comparison value of 0.75 is obtained with a high or very good effective category. In other words, the development of Canva interactive learning media is said to be developing with a percentage of 90%. The level of literacy ability before being given learning media with an average value of 66.37 is classified as low, but after being given learning media, students were given a post-test so that the average score of students was 91.875. It can be concluded that the level of mathematical literacy ability in students of SMP Negeri 3 Tanjung Beringin is classified as high.